2019
DOI: 10.31384/jisrmsse/2019.17.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Role of Trade Openness in Economic Growth of Pakistan

Abstract: Trade openness is a vivid indicator of emerging economies & one of the most important determinants of growth. Therefore, quite a number of researchers have endeavored to analyze the significance & impact of trade openness on economic growth for various economies. Generally, the theoretical framework supports the constructive & positive impact of economic openness of a country for its overall economic development; however, there are mixed outcomes of empirical findings, especially for developing cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…This implies that 1% and 5% increase in trade openness reduces economic growth by 0.060% for Sweden and 0.030% for the United Kingdom. These results are in line with those found by Rigobon and Rodrik (2005) and Ali and Abdullah (2015).…”
Section: The Estimation Of the Var Model For Each Countrysupporting
confidence: 93%
See 1 more Smart Citation
“…This implies that 1% and 5% increase in trade openness reduces economic growth by 0.060% for Sweden and 0.030% for the United Kingdom. These results are in line with those found by Rigobon and Rodrik (2005) and Ali and Abdullah (2015).…”
Section: The Estimation Of the Var Model For Each Countrysupporting
confidence: 93%
“…Rahman et al (2017) found bidirectional relationships between trade openness and economic growth on major developed and developing countries. In contrast, the work by Rodrik, Subramanian, and Trebbi (2004), Chang et al (2009), Amadou (2013), Eris and Ulasan (2013), and Ulasan (2015) found no effect of trade on economic growth in the long run, while Rigobon and Rodrik (2005), Ali and Abdullah (2015) and Rahman, Saidi, and Ben Mbarek (2020) found a negative relationship between international trade and economic growth in the long run.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The above table shows that FDI has positive and significant impact on the economic growth of Pakistan which is referred by the findings of Amina et al,. As well as, Trade openness has a positive and significant effect on economic growth which is referred by the study of Ali et al,(2015). While population positive and significant impact on the economy which is referred by the findings of Ali et al, (2013).…”
mentioning
confidence: 91%
“…while the inflation has a detrimental impact on Pakistan's economy. Moreover, Trade openness has a favorable effect on economic growth, while population has a significant effect on the economy (Ali et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation